Using the Age and Metallicity of 8 Star Clusters to confirm the Chemical Enrichment History of the LMC - Balaha, Farah (2019)
In this paper, we find the ages and metallicities of 8 Large Magellanic Cloud (LMC) star clusters obtained from integrated light spectra and use them to obtain the Chemical Enrichment History of the host galaxy. Our results are in good agreement with those obtained from resolved studies. This confirms that this method can be used for far away galaxies for which their star clusters are not resolved.